FOD Experimental Simulation and Analysis of Potential Benefits of Modified Blisk Geometry - Beranek, Libor; Pitrmuc, Zdenek; Simota, Jan (Manufacturing Technology Journal, 2017)
The article deals with testing of the resistance against Foreign Object Damage (FOD) on leading edges of blisks (blade disks) in turboprop engines made of Ti6Al4V alloy. Such damage can occur during operation, when rapidly rotating compressor parts on the engine intake are exposed to foreign particles. E.g. operation of small passenger aircrafts in desert areas, where large amounts of foreign particles occurs in the atmosphere. The paper describes the development of method for testing the resistance of the leading edge of the blades against FOD in order to mimic the conditions of operational damage. Further it quantifies potential benefits of modification in the geometry of the blisk leading edge and compares results of FOD resistance of sharp leading edge and modified geometry. Results of metallographic analysis for deformed areas near the FOD on Ti6Al4V alloy are also presented.
Keywords: FOD; Foreign Object Damage; Ti6Al4V blisk